2022-RA-831-ESGO Gender-related differences in career development among gynecologic oncology surgeons in europe. European network of young gynecologic oncologists' survey based data. (20th October 2022) - Nikolova, Tanja; Bossart, Michaela; Kacperczyk-Bartnik, Joanna; Razumova, Zoia; Strojna, Alexandra; Bizzari, Nicolo; Pletnev, Andrei; Theofanakis, Charalampos; Gómez-Hidalgo, Natalia; Lanner, Maximilian; Selcuk, Ilker; Shushkevich, Alexander; et al.
Abstract : Introduction/Background: Gender-related differences in career development are well-known issues in various professions. An international survey on gender-related differences was performed among young gynecologic oncologic surgeons in Europe to identify potential gender inequalities in career development. Methodology: A survey on demographics, clinical and academic working environment, family/parenting, career development, salary and leadership was sent to all members of the European Network of Young Gynecologic Oncologists. Gynecologic oncology surgeons and obstetricians/gynecologists who actively work in this field in Europe were included in the study. Results: Responses were analyzed from 192 gynecologic oncology surgeons of whom 125 (65.1%) were female (median age 37, IQR: 34–42) and 67 (34.9%) male (median age 38, IQR: 36–41). Men reported to perform median 15 and women median 10 operations monthly (p = .007). Among women, 24.8% had a leadership position vs. 44.8% among men (crude OR = 2.46, 95% CI 1.31–4.62, p < .01). When stratifying for age under 41 and having children, 36.7% men and 5.6% women had a leadership position (adjusted OR 10.8, 95% CI 3.28–35.64, p < .001). Significantly higher proportion of women than men believed they earned less than their gender counterparts at the same clinical position and with same qualifications (30.4% vs. 2.5%, p < .001). There wasn't a statistically significant difference between academic qualification (PhD degree and/or professorship) and gender ( p = .92 and p = .64), accordingly. In the previous year, men published more peer-reviewed articles than women (median=3 vs. median=2; p = .017). Conclusion: Our comprehensive analysis revealed gender disparity in several aspects among the young generation of gynecologic oncology surgeons, especially pronounced in leadership positions. New initiatives from ENYGO/ESGO are warranted to better understand the attrition of women on the way from training to leadership positions in gynecological oncology, to overcome the identified obstacles and to help elimination of the gender gaps.